An Analysis Of Figurative Language In William Shakespeare’s Sonnets - Muhammad Azzam Al-mujadid; Devian Try Gustary (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Shakespeare's sonnets are renowned for their profound use of rich metaphors and sophisticated language to explore human emotions and experiences. In three well-known sonnets—"Sonnet 18" ("Shall I Compare Thee to a Summer's Day?"), "Sonnet 130" ("My Mistress' Eyes are Nothing Like the Sun"), and "Sonnet 116" ("Let Me Not to the Marriage of True Minds"—this article explores Shakespeare's use of figurative language. Shakespeare's use of metaphors, imagery, and personalization is thoroughly examined in this research using Rasinger's analytical method, revealing the many meanings and feelings that these works contain. Shakespeare's writing prowess and his ongoing relevance in examining the complexity of human existence are highlighted in this article through a thorough examination and comparison of various literary devices